Hadith #1167 - Sunan Ibn Majah - Abu Sa'id al-Khudri; Ayyad bin 'Abdullah bin Sa'd عياض بن عبد الله بن سعد بن أبي سرح; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“The Muslim has six courtesies due from the Muslim: He should greet him with Salam when he meets him; he should accept his invitation if he invites him; he should answer [by Yarhamuk-Allah (may Allah have mercy on you)] to him if he sneezes (and says Al- Hamdulillah); he should visit him if he falls sick; he should follow his funeral if he dies; and he should love for him what he loves for himself.”
Grade:

Hadith #1168 - Sunan Ibn Majah - Abu Hurairah; Abu Sufyan ibn Harb; Da'ud bin Rshyd داود بن رشيد; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hafs bin Ghyath حفص بن غياث; Jabir ibn 'Abdullah; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
“The Muslim has four things due from the Muslim: He should answer [by saying Yarhamuk-Allah (may Allah have mercy on you)] to him if he sneezes (and says Al-Hamdulillah); he should accept his invitation if he invites him; he should attend his funeral if he dies; and he should visit him if he falls sick.”
Grade:

Hadith #1169 - Sunan Ibn Majah - Abdur Rahman bin Muhammad al-Maharbi عبد الرحمن بن محمد بن زياد المحاربي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Hasan al-Basri الحسن البصري; Isma'il bin Muslima إسماعيل بن مسلمة بن قعنب الحارثي القعنب; Jabir ibn 'Abdullah (Sunan Ibn Majah)
“Five are the rights of the Muslim: Returning his greeting, accepting his invitation; attending his funeral; visiting the sick; and answering (saying Yarhamuk-Allah) to the one who sneezes, if he praises Allah (says Al-Hamdu Lillah).”
Grade:

Hadith #1170 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Rashidayn bin Sa'd al-Mahri al-Qayni رشدين بن سعد القيني; Sahl bin Mua'dh bin Ans سهل بن معاذ بن أنس الجهني; Zban bin Fa'id زبان بن فائد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) came walking to visit me (when I was sick), as did Abu Bakr, when I was with Banu Salimah.
Grade:

Hadith #1171 - Sunan Ibn Majah - Anas ibn Malik; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Ibn Majah)
“The Prophet (ﷺ) did not visit any sick person until after three days.”
Grade:

Hadith #1172 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Ja'far bin Muhammad bin 'Ali جعفر بن محمد بن علي - الصادق; Muhammad bin 'Ali b. al-Hussain al-Baqir محمد بن علي بن الحسين بن علي ,الباقر; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Ibn Majah)
“When you enter upon one who is sick, cheer him up and give him hope of a long life, for that does not change anything (of the Divine Decree), but it will cheer the heart of the one who is sick.”
Grade:

Hadith #1173 - Sunan Ibn Majah - Dmrh bin Sa'id bin Aby ضمرة بن سعيد بن أبي حنة; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Ibn Majah)
“What do you long for?” He said: “I long for wheat bread.” The Prophet (ﷺ) said: “Whoever has any wheat bread, let him send it to his brother.” Then the Prophet (ﷺ) said: “If any sick person among you longs for something, then feed him.”
Grade:

Hadith #1174 - Sunan Ibn Majah - Abu Anbh; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Hudayr bin Karayb Abu al-Zahriyya حدير بن كريب أبو الزاهرية; Sa'id bin Sinan al-Hanfi سعيد بن سنان الحنفي (Sunan Ibn Majah)
“The Prophet (ﷺ) entered upon a sick person to visit him. He said: ‘Do you long for anything? Do you long for Ka’k (a type of bread)?’ He said: ‘Yes.’ So they sent someone to bring some Ka’k for him.”
Grade:

Hadith #1175 - Sunan Ibn Majah - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Ibn Majah)
“The Prophet (ﷺ) said to me: ‘When you enter upon one who is sick, tell him to pray for you, for his supplication is like the supplication of the angels.’”
Grade:

Hadith #1176 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘Whoever comes to his Muslim brother and visits him (when he is sick), he is walking among the harvest of Paradise until he sits down, and when he sits down he is covered with mercy. If it is morning, seventy thousand angels will send blessing upon him until evening, and if it is evening, seventy thousand angels will send blessing upon him until morning.’”
Grade:

Hadith #1177 - Sunan Ibn Majah - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin 'Uthman عمرو بن عثمان بن عفان; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Ibn Majah)
‘Whoever visits a sick person, a caller calls from heaven: ‘May you be happy, may your walking be blessed, and may you occupy a dignified position in Paradise.’”
Grade:

Hadith #1178 - Sunan Ibn Majah - Abdullah bin 'Umar bin Hafs bin 'Asim عبد الله بن عمر بن حفص بن عاصم; ibn Umar; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Nafie' نافع مولى ابن عمر; Sa'id bin Abi Maryam سعيد بن أبي مريم (Sunan Ibn Majah)
‘Urge your dying ones to say La ilaha illallah.”
Grade:

Hadith #1179 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Urge your dying ones to say: “La ilaha illallah.”
Grade:

Hadith #1180 - Sunan Ibn Majah - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Ahmed bin 'Isa bin Hassan - al-Tastari أحمد بن عيسى بن حسان - التستري; Jabir ibn 'Abdullah; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Usayd bin Abi Usayd أسيد بن أبي أسيد البراد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Urge your dying ones to say: “La ilaha illallahul-Halimul-Karim, Subhan-Allahi Rabbil-‘Arshil-‘Azim, Al-Hamdu Lillahi Rabbil-‘alamin (None has the right to be worshipped but Allah, the Forbearing, the Most Kind. Glory is to Allah, Lord of the magnificent Throne; praise is to Allah, the Lord of the worlds).’” They said: ‘O Messenger of Allah, what about those who are alive?’ He said: ‘Even better, even better.’”
Grade:

Hadith #1181 - Sunan Ibn Majah - Abu Hurairah; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Muhammad bin Bashar Bindar محمد بن بشار بندار (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘When you visit one who is sick or dying, say good things, for the angels say: Amin to whatever you say.’ When Abu Salamah died, I came to the Prophet (ﷺ) and said: ‘O Messenger of Allah! Abu Salamah has died.’ He said: ‘Say: “Allahummaghfir li wa lahu, wa a’qibni minhu ‘uqba hasanah (O Allah, forgive me and him, and compensate me with someone better than him).’” She said: ‘I said that, and Allah compensated me with someone better tha
Grade:

Hadith #1182 - Sunan Ibn Majah - al-Hasan al-Basri الحسن البصري; Nasr bin 'Ali bin Nasr bin 'Ali; Nwh bin Qays bin نوح بن قيس بن; Qatada قتادة; Samra bin Jundub (Sunan Ibn Majah)
“Recite Qur’an near your dying ones,” meaning Ya-Sin.
Grade:

Hadith #1183 - Sunan Ibn Majah - Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Hajjaj bin Artah حجاج بن أرطاة; ibn Abbas; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Yazid bin Abd Rbh يزيد بن عبد ربه الزبيدي (Sunan Ibn Majah)
“When Ka’b was dying, Umm Bishr bint Bara’ bin Ma’rur came to him and said: ‘O Abu ‘Abdur-Rahman! If you meet so-and-so, convey Salam to him from me.’ He said: ‘May Allah forgive you, O Umm Bishr! We are too busy to think of that.’ She said: ‘O Abu ‘Abdur-Rahman! Did you not hear the Messenger of Allah (ﷺ) say: “The souls of the believers are in green birds, eating from the trees of Paradise”?’ He said: ‘Yes.’ She said: ‘That is what I mean.’”
Grade:

Hadith #1184 - Sunan Ibn Majah - al-Laith bin Sa'd الليث بن سعد; ibn Umar; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر; Nafie' نافع مولى ابن عمر (Sunan Ibn Majah)
“I entered upon Jabir bin ‘Abdullah when he was dying, and I said: ‘Convey my Salam to the Messenger of Allah (ﷺ).’”
Grade:

Hadith #1185 - Sunan Ibn Majah - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Umar; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“Do not grieve for your relative, for that is part of his Hasanat (merits).”
Grade:

Hadith #1186 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Ibn Majah)
“The believer dies with sweat on his brow.”
Grade:

Hadith #1187 - Sunan Ibn Majah - Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Ibn Majah)
“I asked the Messenger of Allah (ﷺ): ‘When does a person stop recognizing people?’ he said: ‘When he sees.”
Grade:

Hadith #1188 - Sunan Ibn Majah - Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) entered upon Abu Salamah (after he had died), and his eyes were wide open. He closed his eyes, then he said: ‘When the soul is taken, the sight follows it.’”
Grade:

Hadith #1189 - Sunan Ibn Majah - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; al-Sa'ib bin Yazid bin Akht Namr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibn Ishaq محمد بن إسحاق بن يسار‎; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Sulaiman bin Hayan al-Azdi سليمان بن حيان الأزدي; Yusuf bin Musa bin Rashid al-Qatan يوسف بن موسى بن راشد القطان (Sunan Ibn Majah)
“When you come to your dead ones, close their eyes, for the sight follows the soul. And say good things, for the Angels say Amin to what the members of the household say.”
Grade:

Hadith #1190 - Sunan Ibn Majah - Aban bin Tghlb أبان بن تغلب; Abdullah bin Mubarak عبد الله بن المبارك; Ady bin Thabit al-Ansari عدي بن ثابت الأنصاري الكوفي; al-Hythm bin Jmyl الهيثم بن جميل; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) kissed ‘Uthman bin Maz’un when he had died, and it is as if I can see him with his tears flowing down his cheeks.”
Grade:

Hadith #1191 - Sunan Ibn Majah - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
It was narrated from Ibn ‘Abbas and ‘Aishah that Abu Bakr kissed the Prophet (ﷺ) when he died.
Grade:

Hadith #1192 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Khalid bin Mukhallad al-Qatwani خالد بن مخلد القطواني (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) entered upon us when we were washing his daughter Umm Kulthum. He said: ‘Wash her three or five times, or more than that if you think you need to, with water and lote leaves, and put camphor or a little camphor in (the water) for the last washing. When you have finished, call for me.’ When we finished, we called him, and he gave his waist-wrapper to us and said: ‘Shroud her with it.’”
Grade:

Hadith #1193 - Sunan Ibn Majah - Abdullah bin Saalam; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Salm Abi al-Nadr سالم بن أبي أمية - أبو النضر (Sunan Ibn Majah)
“Hafsah narrated to me, from Umm ‘Atiyyah” and it is similar to the Hadith of Muhammad. And in the narration of Hafsah it says: “Wash her an odd number of times.” And: “Wash her face three or five times.” And “Start on her right, with the places washed in ablution.” And it says that Umm ‘Atiyyah said: “And we combed her hair into three braids.”
Grade:

Hadith #1194 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Ata' bin Abi Rabah عطاء بن أبي رباح; Ishaq bin Sulaiman al-Razi إسحاق بن سليمان الرازي (Sunan Ibn Majah)
“The Prophet (ﷺ) said to me: ‘Do not show your thigh, and do not look at the thigh of anyone, living or dead.’”
Grade:

Hadith #1195 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Musayb bin Rafa'i al-Asadi المسيب بن رافع الأسدي الكاهلي أبو العلاء; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Umm Habibah bint Abi Sufyan; Unbasa bin Abi Sufyan; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
‘Let the honest wash your dead.”
Grade:

Hadith #1196 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah (Sunan Ibn Majah)
“Whoever washes a deceased person, shrouds him, embalms him, carries him and offers the funeral prayer for him, and does not disclose what he has seen, he will emerge from his sins as on the day his mother bore him.”
Grade:

Hadith #1197 - Sunan Ibn Majah - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; ibn Umar; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“Whoever washes a dead person, let him take a bath.”
Grade:

Hadith #1198 - Sunan Ibn Majah - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Anas bin Sirin أنس بن سيرين الأنصاري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar (Sunan Ibn Majah)
“If I had known then what I know now, no one would have washed the Prophet (ﷺ) but his wives.”
Grade:

Hadith #1199 - Sunan Ibn Majah - al-Laith bin Sa'd الليث بن سعد; Hafsa bint Umar; ibn Umar; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر; Nafie' نافع مولى ابن عمر (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) came back from Al-Baqi’ and I had a headache and was saying: ‘O my head!’ He said: ‘Rather, I should say, O my head, O ‘Aishah!’ Then he said: ‘It will not matter if you were to die before me, for I will take care of you, wash you, shroud you, offer the funeral prayer for you and bury you.’”
Grade:

Hadith #1200 - Sunan Ibn Majah - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي (Sunan Ibn Majah)
“When they started to wash the Prophet (ﷺ), a voice called out from inside (the house) saying: ‘Do not remove the shirt of the Messenger of Allah.’”
Grade:

Hadith #1201 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Khlyl bin 'Amr al-Thqfy الخليل بن عمرو الثقفي; Ali ibn Abi Talib; Sharayk bin 'Abdullah شريك بن عبد الله النخعي (Sunan Ibn Majah)
“May my father be sacrificed for you, you are pure; you were pure in life and you are pure in death.”
Grade:

Hadith #1202 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Abu Hurairah; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني; Yazid bin Kysan al-Yshkry يزيد بن كيسان اليشكري أبو إسماعيل (Sunan Ibn Majah)
“When I die, then wash me with seven buckets from me well, the well of Ghars.”
Grade:

Hadith #1203 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ahmed bin Snan bin Asad أحمد بن سنان بن أسد; ibn Umar; Muhammad bin ''Aabadh محمد بن عبادة; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Ibn Majah)
“They used to claim that he was shrouded in Hibarah.” ‘Aishah said: “They brought a Hibarah Burd, but they did not shroud him in it.”
Grade:

Hadith #1204 - Sunan Ibn Majah - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) was shrouded in three thin white Suhuli cloths.”
Grade:

Hadith #1205 - Sunan Ibn Majah - Abu Hurairah; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Azhar bin al-Qasim al-Rasby أزهر بن القاسم الراسبي; Bakr bin Khlf al-Basri بكر بن خلف البصري; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Zakaria bin Ishaq al-Makki زكريا بن إسحاق المكي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) was shrouded in three garments: The shirt in which he died, and a Najrani Hullah.
Grade:

Hadith #1206 - Sunan Ibn Majah - Abu Hurairah; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“The best of your garments are those which are white, so shroud your dead in them, and wear them.”
Grade:

Hadith #1207 - Sunan Ibn Majah - Abdullah bin Sarjis al-Mazni; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Asim al-Ahwal عاصم الأحول; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan Ibn Majah)
“The best of shrouds is the Hullah (two-piecer).”
Grade:

Hadith #1208 - Sunan Ibn Majah - Abdullah bin Buhayna; Hafs bin 'Asim bin 'Umar حفص بن عاصم بن عمر; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin 'Uthman bin Khalid محمد بن عثمان بن خالد; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن (Sunan Ibn Majah)
“If anyone of you is charged with taking care of his brother (after death), let him shroud him well.”
Grade:

Hadith #1209 - Sunan Ibn Majah - Abdullah bin Numayr عبد الله بن نمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث (Sunan Ibn Majah)
“When Ibrahim the son of the Prophet (ﷺ) died, the Prophet (ﷺ) said to them: ‘Do not wrap him in his shroud until I look at him.’ He came to him, bent over and wept.”
Grade:

Hadith #1210 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Abu Hurairah; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني; Yazid bin Kysan al-Yshkry يزيد بن كيسان اليشكري أبو إسماعيل (Sunan Ibn Majah)
“If one of the members of his family died, Hudhaifah would say: ‘Do not inform anyone of it, for I am afraid that that would be a public death announcement. I heard the Messenger of Allah (ﷺ) with these two ears of mine forbidding making public death announcements.’”
Grade:

Hadith #1211 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Qabus bin Abi al-Makharq/al-Makharq قابوس بن أبي المخارق (Sunan Ibn Majah)
‘Hasten with the funeral (procession), for if the person was righteous then you are advancing him towards good, and if he was otherwise then it is evil which you are taking off of your necks.”
Grade:

Hadith #1212 - Sunan Ibn Majah - Abu Ayyub al-Ansari; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ibrahim al-Nakha'i إبراهيم النخعي; S'hm bin Mnjab bin Rashid سهم بن منجاب بن راشد; Ubaid'h bin Ma'tb عبيدة بن معتب; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“ ‘Abdullah bin Mas’ud said: ‘Whoever follows a funeral (procession), let him carry all (four) corners of it (in turn), for that is Sunnah. Then if he wishes let him voluntarily carry it, and if he wishes let him not do so.’”
Grade:

Hadith #1213 - Sunan Ibn Majah - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Aisha bint Abi Bakr; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin Ma'mar bin Rabi' محمد بن معمر بن ربعي القيسي البحراني; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Qays bin al-Rabi' al-'Asady Abu قيس بن الربيع الأسدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zayd bin Akhzm زيد بن أخزم (Sunan Ibn Majah)
“You should move with tranquility.”
Grade:

Hadith #1214 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) saw some people riding on their animals in a funeral (procession). He said: ‘Do you not feel ashamed that the angels of Allah are walking on foot and you are riding?’”
Grade:

Hadith #1215 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin 'Abdullah bin al-Muhajir محمد بن عبد الله بن المهاجر; Umm Habibah bint Abi Sufyan; Unbasa bin Abi Sufyan; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘The rider should travel behind the funeral (procession) but the one who is walking may walk wherever he wants.”
Grade:

Hadith #1216 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“I saw the Prophet (ﷺ), Abu Bakr and ‘Umar walking ahead of the funeral (procession).”
Grade:

Hadith #1217 - Sunan Ibn Majah - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abdullah bin Mughfal al-Mazni; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Kahmas bin al-Hasan al-Tamimi كهمس بن الحسن التميمي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ), Abu Bakr, ‘Umar and ‘Uthman used to walk ahead of the funeral (procession).”
Grade:

Hadith #1218 - Sunan Ibn Majah - Ali bin Zayd bin 'Abdullah bin Zuhayr علي بن زيد بن عبد الله بن زهير; Anas ibn Malik; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
‘The funeral should be followed and should not follow. There should be no one with it who walks ahead of it.”
Grade:

Hadith #1219 - Sunan Ibn Majah - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Aisha bint Abi Bakr; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Y'aqub bin Ibrahim bin Kathir يعقوب بن إبراهيم بن كثير بن زيد الدورقي (Sunan Ibn Majah)
“We went out with the Messenger of Allah (ﷺ) to attend a funeral, and he saw some people who had cast aside their upper sheets and were walking in their shirts only. The Messenger of Allah (ﷺ) said: ‘Are you adopting the practice of the days of ignorance?’ or; ‘Are you imitating the behavior of the days of ignorance? I was about to supplicate against you that you would return in a different form.’ So they put their sheets back on and never did that again.”
Grade:

Hadith #1220 - Sunan Ibn Majah - Abd al-Whab bin al-Dhak عبد الوهاب بن الضحاك بن أبان; Asim bin 'Umar bin Qatada al-Ansari عاصم بن عمر بن قتادة; Ibn Ishaq محمد بن إسحاق بن يسار‎; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Mahmud bin Labid bin 'Uqba; Rafi' bin Khadij bin Rafi' (Sunan Ibn Majah)
“Do not delay the funeral once it is ready.”
Grade:

Hadith #1221 - Sunan Ibn Majah - Abdur Rahman bin Waqd عبد الرحمن بن واقد بن مسلم البغدادي; Ahmed bin al-Azhar bin Mny' أحمد بن الأزهر بن منيع; Asim bin Abu al-Najud; Muhammad bin al-Mu'ml bin al-Sbah محمد بن المؤمل بن الصباح; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة (Sunan Ibn Majah)
“Abu Musa Ash’ari left instructions, when he was dying, saying: ‘Do not follow me with a censer.’* They said to him: ‘Did you hear something concerning that?’ He said: ‘Yes, from the Messenger of Allah (ﷺ).’”
Grade:

Hadith #1222 - Sunan Ibn Majah - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“Whoever has the funeral prayer offered for him by one hundred Muslims, he will be forgiven.”
Grade:

Hadith #1223 - Sunan Ibn Majah - Abdullah bin Marrah/Abi Marrah عبد الله بن مرة أو بن أبي مرة; Abdullah bin Rashid عبد الله بن راشد الزوفي; al-Laith bin Sa'd الليث بن سعد; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Ibn Majah)
“A son of ‘Abdullah bin ‘Abbas died, and he said to me: ‘O Kuraib! Get up and see if anyone has assembled (to pray) for my son.’ I said: ‘Yes.’ He said: ‘Woe to you, how many do you see? Forty?’ I said: ‘No, rather there are more.’ He said: ‘Take my son out, for I bear witness that I hear the Messenger of Allah (ﷺ) say: “No (group of) forty believers intercede for a believer, but Allah will accept their intercession.”
Grade:

Hadith #1224 - Sunan Ibn Majah - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي (Sunan Ibn Majah)
“If a funeral procession was brought and the number of people who followed it was considered to be small, they would be organized into three rows, then the funeral prayer would be offered.” He said: “The Messenger of Allah (ﷺ) said: ‘No three rows of Muslims offer the funeral prayer for one who has died, but he will be guaranteed (Paradise).’”
Grade:

Hadith #1225 - Sunan Ibn Majah - Abu 'Ubaidah ibn al-Jarrah; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; ibn Mas'ud; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Umar bin 'Abdur Rahman عمر بن عبد الرحمن بن قيس; Uthman bin Muhammad (Sunan Ibn Majah)
“A funeral (procession) passed by the Prophet (ﷺ) and they praised (the deceased) and spoke well of him. He said: ‘(Paradise is) guaranteed for him.’ Then another funeral passed by and they spoke badly of him, and he (the Prophet (ﷺ)) said: ‘(Hell is) guaranteed for him.’ It was said: ‘O Messenger of Allah, you said that (Paradise was) guaranteed for this one and that (Hell was) guaranteed for the other one.’ He said: ‘It is the testimony of the people, and the believers are
Grade:

Hadith #1226 - Sunan Ibn Majah - Abdur Rahman bin Abza; Dhar bin 'Abdullah al-Marhabi ذر بن عبد الله المرهبي; Sa'id bin 'Abdur Rahman bin Abza سعيد بن عبد الرحمن بن أبزي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Talha bin Msrf bin 'Amr طلحة بن مصرف بن عمرو بن كعب; Ubayy ibn Ka'b; Umar bin 'Abdur Rahman عمر بن عبد الرحمن بن قيس; Uthman bin Muhammad; Zubayd bin al-Harith زبيد بن الحارث اليامي (Sunan Ibn Majah)
“A funeral passed by the Prophet (ﷺ) and they praised (the deceased) and spoke well of him and mentioned his good characteristics. He said: ‘(Paradise is) guaranteed for him.’ Then another funeral passed by and they spoke badly of him and mentioned his bad characteristics, and he the Prophet (ﷺ) said: ‘(Hell is) guaranteed for him. You are the witnesses of Allah on earth.’”
Grade:

Hadith #1227 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Abbas; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Jubayr سعيد بن جبير الأسدي; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Ibn Majah)
It was narrated from Samurah bin Jundab Al-Fazari that the Messenger of Allah (ﷺ) offered the funeral prayer for a woman who had died in nifas* and he stood level with her middle (i.e. her waist).” *The postnatal bleeding period.
Grade:

Hadith #1228 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Shababa bin Sawar شبابة بن سوار الفزاري; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Ibn Majah)
“I saw Anas bin Malik offering the funeral prayer for a man, and he stood level with his head. Then another funeral was brought, that of a woman, and they said: ‘O Abu Hamzah! Offer the funeral prayer for her.’ So he stood level with the middle of the bed (the body was upon). ‘Ala’ bin Ziyad said to him: ‘O Abu Hamzah! Is this how you saw the Messenger of Allah (ﷺ) standing in relation to the body of a man and a woman as you have stood?’ He said: ‘Yes.’ Then he turned to us a
Grade:

Hadith #1229 - Sunan Ibn Majah - Abdul 'Aziz bin Jurayj عبد العزيز بن جريج; Khsyf bin 'Abdur Rahman al-Jzry خصيف بن عبد الرحمن; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Ibn Majah)
It was narrated from Ibn ‘Abbas that the Prophet (ﷺ) recited the Opening of the Book (Al-Fatihah) in the funeral prayer.
Grade:

Hadith #1230 - Sunan Ibn Majah - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Anas bin Sirin أنس بن سيرين الأنصاري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) commanded us to recite the Opening of the Book (Al-Fatihah) in the funeral prayer.”
Grade:

Hadith #1231 - Sunan Ibn Majah - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Asim al-Ahwal عاصم الأحول; Ibn Abi al-Shuwarab محمد بن عبد الملك بن أبي الشوارب; ibn Umar; Lahaaq bin Hameed bin Sa'id لاحق بن حميد بن سعيد أبو مجلز (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘When you offer the prayer for the deceased, supplicate sincerely for him.’”
Grade:

Hadith #1232 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي (Sunan Ibn Majah)
“When the Messenger of Allah (ﷺ) offered the funeral prayer he would say: ‘Allahummaghfir lihayyina wa mayyitina, wa shahidina wa gha’ibina, wa saghirina wa kabirina, wa dhakarina wa unthana. Allahumma man ahyaitahu minna fa’ahyihi ‘alal-Islam, wa man tawaffaytahu minna fa tawaffahu ‘alal- iman. Allahumma la tahrimna ajrahu wa la tudillana ba’dah. [O Allah, forgive our living and our dead, those who are present and those who are absent, our young and our old, our males and our fe
Grade:

Hadith #1233 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Shababa bin Sawar شبابة بن سوار الفزاري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) offered the funeral prayer for a man among the Muslims and I heard him say: ‘O Allah, so-and-so the son of so-and-so is in Your case and under Your protection. Protect him from the trial of the grave and the torment of the Fire, for You are the One Who keeps the promise and You are the Truth. Forgive him and have mercy on him, for You are the Oft-Forgiving, Most Merciful.”
Grade:

Hadith #1234 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Bryd bin Abi Maryam بريد بن أبي مريم مالك; Hassan ibn Ali bin Abi Talib; Sharayk bin 'Abdullah شريك بن عبد الله النخعي (Sunan Ibn Majah)
“I saw the Messenger of Allah (ﷺ) offering the funeral prayer for a man among the Ansar, and I heard him say: ‘Allahumma salli ‘alayhi waghfirlahu warhamhu, wa ‘afihi wa’fu ‘anhu, waghsilhu bi ma’in wa thaljin wa baradin, wa naqqihi min adh-dhunubi wal-khataya kama yunaqqath-thawbul-abyadu minad-danas, wa abdilhu bi darihi daran khayran min darihi, wa ahlan khayran min ahlili, wa qihi fitnatal-qabri wa ‘adhaban-nar. (O Allah, send blessing upon him, forgive him, have mercy on h
Grade:

Hadith #1235 - Sunan Ibn Majah - Hammad bin Salama حماد بن سلمة (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ), Abu Bakr and ‘Umar did not give us so much leeway in anything as they did with regard to the prayer for the deceased,” meaning that there was nothing affixed.
Grade:

Hadith #1236 - Sunan Ibn Majah - Anas ibn Malik; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
It was narrated from ‘Uthman bin ‘Affan that the Prophet (ﷺ) offered the funeral prayer for ‘Uthman bin Maz’un, and he said four Takbir over him.
Grade:

Hadith #1237 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; ibn Abbas; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Salah bin Hasaan al-Nadri صالح بن حسان النضري (Sunan Ibn Majah)
“I prayed with ‘Abdullah bin Abi Awfa Al-Aslami, the Companion of the Messenger of Allah (ﷺ), offering the funeral prayer for a daughter of his. He said Takbir over her four times, and he paused for a while after the fourth. I heard the people saying Subhan- Allah to him throughout the rows. Then he said the Salam and said: ‘Did you think that I was going to say a fifth Takbir?’ They said: ‘We were afraid of that.’ He said: ‘I was not going to do that, but the Messenger of Allah
Grade:

Hadith #1238 - Sunan Ibn Majah - Abdur Rahman bin Abza; Ali bin Maymun al-Rqy علي بن ميمون الرقي; Mkhld bin Yazid al-Quraishi مخلد بن يزيد القرشي الحراني; Sa'id bin 'Abdur Rahman bin Abza سعيد بن عبد الرحمن بن أبزي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubayy ibn Ka'b; Zubayd bin al-Harith زبيد بن الحارث اليامي (Sunan Ibn Majah)
It was narrated from Ibn ‘Abbas that the Prophet (ﷺ) said Takbir four times.
Grade:

Hadith #1239 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Nasr bin 'Ali bin Nasr bin 'Ali; Sahl bin Yusuf al-Anmaty سهل بن يوسف الأنماطي (Sunan Ibn Majah)
“Zaid bin Arqan used to say the Takbir four times in the funeral prayer, and he said the Takbir five times for one funeral. I asked him (about that) and he said: ‘The Messenger of Allah (ﷺ) used to do that.’”
Grade:

Hadith #1240 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Ayoub al-Sakhtiyani أيوب السختياني; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan Ibn Majah)
It was narrated from Kathir bin ‘Abdullah, from his father, from his grandfather, that the Messenger of Allah (ﷺ) said the Takbir five times.
Grade:

Hadith #1241 - Sunan Ibn Majah - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Masrouq bin al-Ajda' مسروق بن الأجدع; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘The (funeral) prayer should be offered for a child.’”
Grade:

Hadith #1242 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“If a child utters a sound (after being born), the funeral prayer should be offered for him and (his relatives) may inherit from him.”
Grade:

Hadith #1243 - Sunan Ibn Majah - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; Jabir ibn 'Abdullah; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Talha bin Nafi' Abi Sufyan al-Askaf طلحة بن نافع الواسطي أبو سفيان الإسكاف (Sunan Ibn Majah)
“The Prophet (ﷺ) said: ‘Offer the (funeral) prayer for your children, for they have gone ahead of you (i.e. to prepare your place in Paradise for you).”
Grade:

Hadith #1244 - Sunan Ibn Majah - Abdur Rahman bin Zayd bin Aslam عبد الرحمن بن زيد بن أسلم العدوي; Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“I said to ‘Abdullah bin Abi Awfa: ‘Did you see Ibrahim, the son of the Messenger of Allah (ﷺ)?’ He said: ‘He died when he was small, and if it had been decreed that there should be any Prophet after Muhammad (ﷺ), his son would have lived. But there is no Prophet after him.’”
Grade:

Hadith #1245 - Sunan Ibn Majah - Abdur-Razzaq عبد الرزاق بن همام; Abu Sa'id al-Khudri; Ahmed bin al-Azhar bin Mny' أحمد بن الأزهر بن منيع; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“Then Ibrahim the son of the Messenger of Allah (ﷺ) died, the Messenger of Allah (ﷺ) prayed and said: ‘He has a wet-nurse in Paradise, and if he had lived he would have been a Siddiq and a Prophet. If he had lived his maternal uncles, the Egyptians, would have been set free and no Egyptian would ever have been enslaved.’”
Grade:

Hadith #1246 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Ayyub al-Ansari; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Muhammad bin Yusuf al-Faryabi محمد بن يوسف الفريابي (Sunan Ibn Majah)
“When Qasim the son of the Messenger of Allah (ﷺ) died, Khadijah said: ‘O Messenger of Allah, the milk of Qasim’s mother is overflowing. Would that Allah had let him live until he had finished breastfeeding.’ The Messenger of Allah (ﷺ) said: ‘He will complete his breastfeeding in Paradise.’ She said: ‘If I know that, O Messenger of Allah, it makes it easier for me to bear.’ The Messenger of Allah (ﷺ) said: ‘If you wish, I will pray to Allah to let you hear his voice.’ S
Grade:

Hadith #1247 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Qatada قتادة; Sa'd bin Hisham bin 'Amir سعد بن هشام بن عامر; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Zararah bin Awfa al-'Amiri al-Harshi زرارة بن أوفى العامري الحرشي (Sunan Ibn Majah)
“They (the martyrs) were brought to the Messenger of Allah (ﷺ) on the Day of Uhud, and he started to offer the funeral prayer for them, ten by ten. Hamzah lay where he lay, and they were taken away but he was left where he was.”
Grade:

Hadith #1248 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Hakam bin 'Utayba الحكم بن عتيبة; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Maqsim bin Bajra مقسم بن بجرة; Umm Salamah; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Ibn Majah)
“Which of them had memorized more Qur’an?” And if one of them was pointed out to him, he would put him in the niche-grave first. And he said: “I am a witness over them.” He commanded that they should be buried with their blood, and that the funeral prayer should not be offered for them and they should not be washed.
Grade:

Hadith #1249 - Sunan Ibn Majah - Ahmed bin Snan bin Asad أحمد بن سنان بن أسد; ibn Umar; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Jabir ibn 'Abdullah; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
It was narrated from Ibn ‘Abbas that the Messenger of Allah (ﷺ) commanded that the weapons and armor should be removed from the slain of Uhud, and they should be buried in their clothes stained with blood.
Grade:

Hadith #1250 - Sunan Ibn Majah - Amir al-Sha'bi عامر الشعبي; ibn Abbas; ibn Umar; Isma'il bin Musa al-Fazari al-Siddi إسماعيل بن موسى الفزاري السدي; Jabir ibn 'Abdullah; Sharayk bin 'Abdullah شريك بن عبد الله النخعي (Sunan Ibn Majah)
“I heard Jabir bin ‘Abdullah say: ‘The Messenger of Allah (ﷺ) commanded that the slain of the battle of Uhud should be returned to the battlefield; they had been moved to Al-Madinah.’”
Grade:

Hadith #1251 - Sunan Ibn Majah - al-Hasan al-Basri الحسن البصري; Hmad bin Ms'd'h al-Tmymy حماد بن مسعدة التميمي; Khayra Umm al-Hasan al-'Abbassri خيرة أم الحسن البصري; Maymun bin Musa ميمون بن موسى; Muhammad bin Bashar Bindar محمد بن بشار بندار; Umm Salamah (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Whoever offers the funeral prayer in the mosque will have nothing (i.e., no reward).’”
Grade:

Hadith #1252 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Umar bin Abd al-Wahd عمر بن عبد الواحد بن قيس السلمي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“By Allah! The Messenger of Allah (ﷺ) did not offer the funeral prayer for Suhail bin Baida’ anywhere but in the mosque.”
Grade:

Hadith #1253 - Sunan Ibn Majah - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Mas'ar bin Kadam مسعر بن كدام; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Sufyan bin 'Uyaynah سفيان بن عيينة; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“There are three times during the day when the Messenger of Allah (ﷺ) forbade us to offer the funeral prayer or bury our dead: When the sun has fully risen (until it is higher up in the sky), when it is overhead at noon until it has passed the meridian, and when it is starting to set until it has set.”
Grade:

Hadith #1254 - Sunan Ibn Majah - Abdur Rahman bin Ishaq عبد الرحمن بن إسحاق بن عبد الله; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
It was narrated from Ibn ‘Abbas that the Messenger of Allah (ﷺ) placed a man in his grave at night, and he lit a lamp in his grave.
Grade:

Hadith #1255 - Sunan Ibn Majah - Abu Hurairah; al-Nadr bin Shumayl al-Maazni النضر بن شميل المازني أبو الحسن النحوي; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Ibn Majah)
“Do not bury your dead at night unless you are forced to.”
Grade:

Hadith #1256 - Sunan Ibn Majah - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Bakr bin 'Umar أبو بكر بن عمر بن عبد الرحمن; Ahmed bin Snan bin Asad أحمد بن سنان بن أسد; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'id bin Yasar, Abu al-Hubab سعيد بن يسار أبو الحباب (Sunan Ibn Majah)
“Offer the funeral prayer for your dead by night or by day.”
Grade:

Hadith #1257 - Sunan Ibn Majah - Aabad bin Mnswr عباد بن منصور; ibn Abbas; Ikrama عكرمة; Muhammad bin Yazid bin 'Abdul Malik محمد بن يزيد بن عبد الملك; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي (Sunan Ibn Majah)
“When ‘Abdullah bin Ubayy died, his son came to the Prophet (ﷺ) and said: ‘O Messenger of Allah, give me your shirt so that I may shroud him in it.’ The Messenger of Allah (ﷺ) said: ‘Notify me when he is ready (i.e., when he has been washed and shrouded).’ When the Prophet (ﷺ) wanted to offer the funeral prayer for him: ‘You should not do that.’ The Prophet (ﷺ) offered the funeral prayer for him, and the Prophet (ﷺ) said to him: ‘I have been given two choices: “…a
Grade:

Hadith #1258 - Sunan Ibn Majah - Abdullah bin Muhammad bin 'Aqil عبد الله بن محمد بن عقيل بن أبي طالب; Jabir ibn 'Abdullah; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Ibn Majah)
“The leader of the hypocrites in Al- Madinah died, and left instructions that the Prophet (ﷺ) should offer the funeral prayer for him and shroud him in his shirt. He offered the funeral prayer for him and shrouded him in his shirt, and stood by his grave. Then Allah revealed the words: ‘And never pray (the funeral prayer) for any of them (hypocrites) who dies, nor stand at his grave.”
Grade:

Hadith #1259 - Sunan Ibn Majah - ibn Umar; Muhammad bin 'Aabad bin Musa محمد بن عباد بن موسى; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
‘Offer prayer for everyone who dies, and strive in Jihad under every chief.”
Grade:

Hadith #1260 - Sunan Ibn Majah - Ali bin Ms'hr علي بن مسهر; Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
It was narrated from Jabir bin Samurah that a man from among the Companions of the Prophet (ﷺ) was wounded, and the wound caused him a great deal of pain. He went and took a spearhead, and slaughtered himself with it. The Prophet (ﷺ) did not offer the funeral prayer for him, and that was as an admonition for others.
Grade:

Hadith #1261 - Sunan Ibn Majah - Amr bin Rafa'i al-Advi. Client Of 'Umar عمرو بن رافع العدوي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“Why did you not tell me?” Then he went to her grave and offered the funeral prayer for her.
Grade:

Hadith #1262 - Sunan Ibn Majah - Abdur Rahman bin 'Abdul Malik bin Shayb عبد الرحمن بن عبد الملك بن شيبة; al-Hakam bin 'Utayba الحكم بن عتيبة; Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Ibn Majah)
“We went out with the Prophet (ﷺ) and when we reached Al-Baqi’, we saw a new grave. He asked about it and they said: ‘(It is) so-and-so (a woman).’ He recognized the name and said: ‘Why did you not tell me about her?’ They said: ‘You were taking a nap and you were fasting, and we did not like to disturb you.’ He said: ‘Do not do that; I do not want to see it happen again that one of you dies, while I am still among you, and you do not tell me, for my prayer for him is a mercy
Grade:

Hadith #1263 - Sunan Ibn Majah - Abdullah bin Buhayna; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sufyan bin 'Uyaynah سفيان بن عيينة; Uthman bin Muhammad (Sunan Ibn Majah)
“Why did you not tell me?” Then he said to his Companions: “Line up in rows to pray for her,” and he offered the funeral prayer for her.
Grade:

Hadith #1264 - Sunan Ibn Majah - Abdullah bin Buhayna; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman bin Hayan al-Azdi سليمان بن حيان الأزدي; Uthman bin Muhammad; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“A man died whom the Messenger of Allah (ﷺ) used to visit, and they buried him at night. When morning came, they told him. He said: ‘What kept you from telling me?’ They said: ‘It was night and it was dark, and we did not like to cause you any inconvenience.’ Then he went to the grave and offered the funeral prayer for him.”
Grade:

Hadith #1265 - Sunan Ibn Majah - al-Mughira bin Shbl المغيرة بن شبل; al-Mughira ibn Shu'ba; Jabir ibn 'Abdullah; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Muhammad bin Yusuf al-Baykandi محمد بن يوسف البيكندي البخاري; Qays bin Abi Hazim قيس بن أبي حازم; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
It was narrated from Anas that the Prophet (ﷺ) offered the funeral prayer at a grave after the burial.
Grade:

Hadith #1266 - Sunan Ibn Majah - Abdur Rahman Ibn 'Awf; ibn Abbas; Ibn Ishaq محمد بن إسحاق بن يسار‎; Karayb bin Abi Muslim كريب بن أبي مسلم الهاشمي; Makhul al-Shami/al-Damashiqi مكحول الشامي; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Ibn Majah)
It was narrated from Ibn Buraidah from his father that the Prophet (ﷺ) offered the funeral prayer for a deceased person after he had been buried.
Grade:

Hadith #1267 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sulaiman bin Hayan al-Azdi سليمان بن حيان الأزدي; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“There was a black woman who used to sweep the mosque, and she passed away at night. The following morning the Messenger of Allah (ﷺ) was told of her death. He said: ‘Why did you not call me?’ Then he went out with his Companions and stood at her grave, and said Takbir over her, with the people behind him, and he supplicated for her, then he went away.’”
Grade:

Hadith #1268 - Sunan Ibn Majah - Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Najashi has died.’ The Messenger of Allah (ﷺ) and his Companions went out to Al-Baqi’, and we lined up in rows behind him, and the Messenger of Allah (ﷺ) went forward, then he said four Takbir.”
Grade:

Hadith #1269 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Mas'ar bin Kadam مسعر بن كدام; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Your brother Najashi has died, so offer the funeral prayer for him.” Then he stood and we prayed behind him. I was in the second row and two rows prayed for him.”
Grade:

Hadith #1270 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“Your brother Najashi has died, so stand and pray for him.” So we formed two rows behind him.
Grade:

Hadith #1271 - Sunan Ibn Majah - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Abu Hurairah; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Ibn Sirin محمد بن سيرين الأنصاري (Sunan Ibn Majah)
“Pray for a brother of yours who has died in a land other than yours.” They said: “Who is he?” He said: “Najashi.”
Grade:

Hadith #1272 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin Thabit al-Jhdry أحمد بن ثابت الجحدري; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
It was narrated from Ibn ‘Umar that the Prophet (ﷺ) offered the funeral prayer for Najashi and said four Takbir.
Grade:

Hadith #1273 - Sunan Ibn Majah - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibn Ishaq محمد بن إسحاق بن يسار‎; Sufyan bin Wky' bin al-Jrah سفيان بن وكيع بن الجراح; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Sunan Ibn Majah)
“Whoever offers the funeral prayer will have one Qirat and whoever awaits until (the burial) is finished will have two Qirat.” They said: ‘What are these two Qirat?’ He said: ‘Like two mountains.’”
Grade:

Hadith #1274 - Sunan Ibn Majah - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ibn Ishaq محمد بن إسحاق بن يسار‎; Sufyan bin Wky' bin al-Jrah سفيان بن وكيع بن الجراح; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Sunan Ibn Majah)
“Whoever offers the funeral prayer will have one Qirat and whoever attends the burial will have two Qirat.” The Prophet (ﷺ) was asked about the Qirat and he said: “(It is) like Uhud.”
Grade:

Hadith #1275 - Sunan Ibn Majah - Abdur Rahman bin 'Abdul Malik bin Shayb عبد الرحمن بن عبد الملك بن شيبة; Alqama bin Qays علقمة بن قيس بن عبد الله; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
‘Whoever offers the funeral prayer will have one Qirat; and whoever attends until the burial is over, will have two Qirat. By the One in Whose Hand is the soul of Muhammad! The Qirat is greater than this (mountain of) Uhud.”
Grade:

Hadith #1276 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Thawban bin Bujdud; Uthman bin Muhammad; Zuhyr bin Salm al-Nsy زهير بن سالم العنسي بالنون (Sunan Ibn Majah)
“When you see a funeral (procession) stand up for it until it has passed by or it is placed on the ground.”
Grade:

Hadith #1277 - Sunan Ibn Majah - Abdullah bin Yazid al-Makhzumi عبد الله بن يزيد المخزومي المقريء; Abu Hurairah; Isa bin Musa Ghanjar عيسى بن موسى غنجار; Muhammad bin 'AR bin Thauban محمد بن عبد الرحمن بن ثوبان; Usamah ibn Zayd; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني (Sunan Ibn Majah)
“A funeral has passed by the Prophet (ﷺ) and he stood up and said: ‘Stand up out of recognition of the enormity of death.’”
Grade:

Hadith #1278 - Sunan Ibn Majah - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Aisha bint Abi Bakr; al-Hythm bin Kharjh الهيثم بن خارجة; Ibn Jurayj ابن جريج; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) stood up for a funeral, and we stood up, until he sat down, then we sat down.”
Grade:

Hadith #1279 - Sunan Ibn Majah - Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Umar bin 'Ali bin Ata'a bin Maqaddam عمر بن علي بن عطاء بن مقدم; Umar bin Shbh عمر بن شبة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“When the Messenger of Allah (ﷺ) followed a funeral, he would not sit down until it had been placed in the niche-grave. A rabbi came to him and said: ‘This is what we do, O Muhammad!’ So the Messenger of Allah (ﷺ) sat down and said: ‘Be different from them.’”
Grade:

Hadith #1280 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Hrmlh bin Yahya bin حرملة بن يحيى; Umar bin Qays al-Mky عمر بن قيس المكي; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“I could not find him, meaning the Prophet (ﷺ), and he was in Al-Baqi’. He said: “As-salamu ‘alaykum dara qawmin mu’minin. Antum lana faratun wa inna bikum lahiqun. Allahumma la tahrimna ajrahum wa la taftinna ba’dahum. (Peace be upon you, O abode of believing people. You have gone ahead of us and verily we will join you soon. O Allah, do not deprive us of their reward and do not put us to trial after them).”
Grade:

Hadith #1281 - Sunan Ibn Majah - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ibrahim bin Tahman إبراهيم بن طهمان; Imran bin Husain; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to teach them, when they went out to the graveyard, to say: As-salamu ‘alaykum ahlad-diyar minal-mu’minina wal- muslimin, wa inna insha’ Allah bikum lahiqun, nas’alul-laha lana wa lakumul-‘afiyah (Peace be upon you, O inhabitants of the abodes, believers and Muslims, and we will join you soon if Allah wills. We ask Allah for well-being for us and for you).’”
Grade:

Hadith #1282 - Sunan Ibn Majah - Ishaq bin Yusuf bin Mrdas إسحاق بن يوسف بن مرداس; Jabir ibn 'Abdullah; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wa'il bin Hujr al-Kundi al-Hadrami (Sunan Ibn Majah)
“We went out with the Messenger of Allah (ﷺ) for a funeral, and he sat facing the Qiblah (prayer direction).”
Grade:

Hadith #1283 - Sunan Ibn Majah - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Umm Salamah (Sunan Ibn Majah)
“We went out with the Messenger of Allah (ﷺ) for a funeral, and we came to a grave. He sat down and we sat down, as if there were birds on our heads.”
Grade:

Hadith #1284 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; al-Walid bin Abi Hisham الوليد بن أبي هشام زياد; Umarh bint 'Abdur Rahman عمرة بنت عبد الرحمن بن سعد بن زرارة (Sunan Ibn Majah)
“When the deceased was placed in the grave, the Prophet (ﷺ) would say: ‘Bismillah, wa ‘ala millati rasul-illah (In the Name of Allah and according to the religion of the Messenger of Allah).’” Abu Khalid said on one occasion, when the deceased was placed in the grave: “Bismillah wa ‘ala sunnati rasul- illah (In the Name of Allah and according to the Sunnah of the Messenger of Allah).” Hisham said in his narration: “Bismillah, wa fi sabil-illah, wa ‘ala millati rasul-illah (
Grade:

Hadith #1285 - Sunan Ibn Majah - Abdul 'Aziz bin Abi Hazim عبد العزيز بن أبي حازم; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Muhammad bin 'Uthman bin Khalid محمد بن عثمان بن خالد; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) placed Sa’d gently in his grave and sprinkled water on it.”
Grade:

Hadith #1286 - Sunan Ibn Majah - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر (Sunan Ibn Majah)
It was narrated from Abu Sa’eed that the Messenger of Allah (ﷺ) was brought into his grave from the direction of the Qiblah, and he was placed in his grave gently.
Grade:

Hadith #1287 - Sunan Ibn Majah - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Babah عبد الله بن باباه; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Ibn Majah)
“I was present with Ibn ‘Umar at a funeral. When the body was placed in the niche-grave) he said, ‘Bismillah wa fi sabil-illah wa ‘ala millati rasul-illah’ (In the Name of Allah, for the sake of Allah and according to the religion of the Messenger of Allah). When he started to place bricks in the niche-grave he said: ‘Allahumma ajirha min ash-shaitani wa min ‘adhabil-qabr. Allahumma Jafil-arda ‘an janbaiha, wa sa’id ruhaha, wa laqqiha minka ridwana (O Allah, protect him from Sa
Grade:

Hadith #1288 - Sunan Ibn Majah - Abdullah ibn Ja'far; Anas ibn Malik; Isma'il bin Muhammad bin Sa'd إسماعيل بن محمد بن سعد بن أبي وقاص الزهر; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘The niche-grave is for us and the ditch-grave is for others.”
Grade:

Hadith #1289 - Sunan Ibn Majah - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Bashr bin Hilal al-Swaf بشر بن هلال الصواف; Imran bin Husain; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘The niche-grave is for us and the ditch-grave is for others.’”
Grade:

Hadith #1290 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ibrahim al-Nakha'i إبراهيم النخعي; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Make a niche-grave for me, and block it up with bricks as was done for the Messenger of Allah (ﷺ).”
Grade:

Hadith #1291 - Sunan Ibn Majah - Abdullah bin Numayr عبد الله بن نمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“When the Prophet (ﷺ) died, there was a man in Al-Madinah who used to make a niche in the grave and another who used to dig graves without a niche. They said: ‘Let us pray Istikharah to our Lord and call for them both, and whichever of them comes first, we will let him do it.’ So they were both sent for, and the one who used to make the niche-grave came first, so they made a niche-grave for the Prophet (ﷺ).”
Grade:

Hadith #1292 - Sunan Ibn Majah - N'ym bin Abi Hnd نعيم بن أبي هند; Nasr bin 'Ali bin Nasr bin 'Ali; Nbyt bin Shryt al-'Ashj'y al-Kwfy; Saalm bin 'Ubaid al-Ashja'i; Salma bin Nabayt سلمة بن نبيط (Sunan Ibn Majah)
“When the Messenger of Allah (ﷺ) died, they differed as to whether his grave should have a niche or a ditch in the ground, until they spoke and raised their voices concerning that. Then ‘Umar said: ‘Do not shout in the presence of the Messenger of Allah (ﷺ), living or dead,’ or words to that effect. So they sent for both the one who made a niche and the one who dug graves without a niche, and the one who used to make a niche came and dug a grave with a niche for the Messenger of Alla
Grade:

Hadith #1293 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; ibn Abbas; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“I came one night to guard the Prophet (ﷺ), and there was a man reciting loudly. The Prophet (ﷺ) came out and I said: ‘O Messenger of Allah, this man is showing off.’ Then he died in Al-Madinah, and they finished preparing him, then they carried his dead body. The Prophet (ﷺ) said: ‘Be gentle with him, may Allah be gentle with him, for he loved Allah and His Messenger.’ Then his grave was dug and he (the Prophet (ﷺ)) said: ‘Make it spacious for him, and may Allah make it spac
Grade:

Hadith #1294 - Sunan Ibn Majah - Bakr bin 'Abdullah al-Mazni بكر بن عبد الله المزني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hamza bin al-Mughira bin Nashayt حمزة بن المغيرة بن نشيط; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“Dig the grave deep, make it spacious and prepare it well.”
Grade:

Hadith #1295 - Sunan Ibn Majah - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
It was narrated from Anas bin Malik that the Messenger of Allah (ﷺ) marked the grave of ‘Uthman bin Maz’un with a rock.
Grade:

Hadith #1296 - Sunan Ibn Majah - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Anas ibn Malik; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade plastering over graves.”
Grade:

Hadith #1297 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Salamah; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Umar bin Abi Salamah (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade writing anything on graves.”
Grade:

Hadith #1298 - Sunan Ibn Majah - al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر (Sunan Ibn Majah)
It was narrated from Abu Sa’eed that the Prophet (ﷺ) forbade building structures over graves.
Grade:

Hadith #1299 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hafs bin Ghyath حفص بن غياث; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
It was narrated from Abu Hurairah that the Messenger of Allah (ﷺ) offered the funeral prayer, then he came to the grave of the deceased and scattered three handfuls of earth from the side of (the deceased’s) head.
Grade:

Hadith #1300 - Sunan Ibn Majah - Abdullah bin Nafi' al-Sa'agh عبد الله بن نافع الصائغ المخزومي; Anbasa bin 'Abdur Rahman bin 'Uayna عنبسة بن عبد الرحمن بن عيينة; Umm Salamah (Sunan Ibn Majah)
The Messenger of Allah (ﷺ) said: “If one of you were to sit on a live coal that burns him, that would be better for him than if he were to sit on a grave.”
Grade:

Hadith #1301 - Sunan Ibn Majah - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
‘If I were to walk on a live coal or a sword, or if I were to sew shows to my feet, that would be better for me than walking on the grave of a Muslim. And I see no difference between relieving myself in the midst of graves or in the middle of the marketplace.”
Grade:

Hadith #1302 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“While I was walking with the Messenger of Allah (ﷺ) he said: ‘O son of Khasasiyyah, why are you angry with Allah when you are walking with the Messenger of Allah?’ I said: ‘O Messenger of Allah! I am not angry with Allah at all. Allah has bestowed all good on me.’ Then he passed by the graves of the Muslims and said: ‘They have caught up with a great deal of good.’ Then he passed by the graves of the idolaters and said: ‘They died before a great deal of good came to them.’ T
Grade:

Hadith #1303 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Dmdm bin Jws ضمضم بن جوس; Ma'mar bin Rashid معمر بن راشد; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“Visit the graves, for they will remind you of the Hereafter.”
Grade:

Hadith #1304 - Sunan Ibn Majah - Aisha bint Abi Bakr; al-Hakam bin 'Abdul Malik الحكم بن عبد الملك القرشي; Ali bin Thabit al-Jzry علي بن ثابت الجزري أبو أحمد; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Ibn Majah)
It was narrated from ‘Aishah that the Messenger of Allah (ﷺ) gave permission for visiting the graves.
Grade:

Hadith #1305 - Sunan Ibn Majah - al-Hythm bin Jmyl الهيثم بن جميل; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Ibn Majah)
It was narrated from Ibn Mas’ud that the Messenger of Allah (ﷺ) said, “I used to forbid you to visit the graves, but now visit them, for they will draw your attention away from this world and remind you of the Hereafter.”
Grade:

Hadith #1306 - Sunan Ibn Majah - Abdullah bin Numayr عبد الله بن نمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Hafs bin 'Asim bin 'Umar حفص بن عاصم بن عمر; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Khbyb bin 'Abdur Rahman خبيب بن عبد الرحمن بن خبيب; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“The Prophet (ﷺ) visited the grave of his mother and wept, causing the people around him to weep. Then he said: ‘I asked my Lord for permission to seek forgiveness for her, but He did not give me permission. Then I asked my Lord for permission to visit her grave and He gave me permission. So visit the graves, for they will remind you of death.’”
Grade:

Hadith #1307 - Sunan Ibn Majah - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Sa'id al-Khudri (Sunan Ibn Majah)
“A Bedouin came to the Prophet (ﷺ) and said: ‘O Messenger of Allah, my father used to uphold the ties of kinship, and so and so forth, where is he?’ He said: ‘In the Fire.’ It was as if he found that difficult to bear. Then he said: ‘O Messenger of Allah. Where is your father?’ The Messenger of Allah (ﷺ) said: ‘Whenever you pass by the grave of an idolater, give him the tidings of Hell-fire.’ The Bedouin later became Muslim, and he said: ‘The Messenger of Allah (ﷺ) gave
Grade:

Hadith #1308 - Sunan Ibn Majah - Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; ibn Abbas; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) cursed women who visit graves.”
Grade:

Hadith #1309 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amr bin 'Absa al-Salmi; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Tlq يزيد بن طلق (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) cursed women who visit graves.”
Grade:

Hadith #1310 - Sunan Ibn Majah - Abu Hurairah; al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; al-Hasan bin Da'ud bin Muhammad الحسن بن داود بن محمد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Sa'id bin Abi Sa'id (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) cursed women who visit graves.”
Grade:

Hadith #1311 - Sunan Ibn Majah - Abdullah al-Snabhy Mkhtlf; Abdur-Razzaq عبد الرزاق بن همام; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Ma'mar bin Rashid معمر بن راشد; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“We were prevented from following the funeral, but that was not made binding on us.”
Grade:

Hadith #1312 - Sunan Ibn Majah - Jubayr bin Mut'im; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin 'Uyaynah سفيان بن عيينة; Yahya bin Hakeem al-Maquuam يحيى بن حكيم المقوم (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) went out and saw some women sitting, and he said: ‘What are you sitting here for?’ They said: ‘We are waiting for the funeral.’ He said: ‘Are you going to wash the deceased?’ They said: ‘No.’ He said: ‘Are you going to lower him into the grave?’ They said: ‘No.’ He said: ‘Then go back with a burden of sin and not rewarded.’”
Grade:

Hadith #1313 - Sunan Ibn Majah - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Asim al-Ahwal عاصم الأحول; ibn Mas'ud; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة (Sunan Ibn Majah)
“And that they will not disobey you in Ma’ruf (all that is good in Islam);” he said: “(It is about) wailing.”
Grade:

Hadith #1314 - Sunan Ibn Majah - Abdullah bin al-Samit عبد الله بن الصامت; Abu 'Imran al-Jauni عبد الملك بن حبيب أبو عمران الجوني; Abu Dharr al-Ghaffari; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“Mu’awiyah delivered a sermon in Hims, and in his sermon he mentioned that the Messenger of Allah (ﷺ) forbade wailing.”
Grade:

Hadith #1315 - Sunan Ibn Majah - Hilal bin Yasaf هلال بن يساف; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubada bin As-Samit (Sunan Ibn Majah)
‘Wailing is one of the affairs of the Days of Ignorance, and if the woman who wails dies without having repented, Allah will cut a garment of pitch (tar) for her and a shirt of flaming fire.’”
Grade:

Hadith #1316 - Sunan Ibn Majah - ibn Umar; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“Wailing over the dead is one of the affairs of the Days of Ignorance and if the woman who wails does not repent before she dies, she will be resurrected on the Day of Resurrection wearing a shirt of pitch (tar), over which she will wear a shirt of flaming fire.”
Grade:

Hadith #1317 - Sunan Ibn Majah - al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sahl bin Abi Hathma; Salah bin Khuwat bin Jubayr صالح بن خوات بن جبير; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade following a funeral that was accompanied by a wailing woman.”
Grade:

Hadith #1318 - Sunan Ibn Majah - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Ayoub al-Sakhtiyani أيوب السختياني; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Ibn Majah)
“He is not one of us who tears his garments, strikes his cheeks, and cries with the cry of the Days of Ignorance.’”
Grade:

Hadith #1319 - Sunan Ibn Majah - Abdullah bin Numayr عبد الله بن نمير; Abu Mas'ud al-Badri; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Qays bin Abi Hazim قيس بن أبي حازم (Sunan Ibn Majah)
It was narrated from Abu Umamah that the Messenger of Allah (ﷺ) cursed the woman who scratches her face and rends her garment and cries that she is doomed (i.e. because of the death of this person).
Grade:

Hadith #1320 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; al-Nu'man bin Bashir ibn Sa'd; Jmyl bin al-Hasan bin Jmyl جميل بن الحسن; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“When Abu Musa fell sick, his wife Umm ‘Abdullah started to wail loudly. He woke up and said to her: ‘Do you not know that I am innocent of those whom the Messenger of Allah (ﷺ) declared innocence of?’ And he told her that the Messenger of Allah (ﷺ) said: ‘I am innocent of those who shave their heads, raise their voices and tear their garments (at times of calamity).’”
Grade:

Hadith #1321 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Urwa ibn al-Zubayr عروة بن الزبير; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Ibn Majah)
It was narrated from Abu Hurairah that the Prophet (ﷺ) was attending a funeral. ‘Umar saw a woman and shouted at her, but the Prophet (ﷺ) said, “Leave her alone, O ‘Umar, for the eye weeps and the heart is afflicted, and the bereavement is recent.”
Grade:

Hadith #1322 - Sunan Ibn Majah - al-Aswad bin Qays al-Bdy الأسود بن قيس العبدي; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Samra bin Jundub; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin 'Aabad ثعلبة بن عباد; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The son of one of the daughters of the Messenger of Allah (ﷺ) was dying. She sent for him, asking him to come to her, and he sent word to her, saying: ‘To Allah belongs what He has taken and to Him belongs what He has given. Everything has an appointed time with Him, so be patient and seek reward.’ But she sent for him again, adjuring him to come. So the Messenger of Allah (ﷺ) got up, and I got up with him, as did Mu’adh bin Jabal, Ubayy bin Ka’b and ‘Ubadah bin Samit. When we e
Grade:

Hadith #1323 - Sunan Ibn Majah - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Asma' bint Abi Bakr (Sunan Ibn Majah)
“When Ibrahim, the son of the Messenger of Allah (ﷺ), died, the Messenger of Allah (ﷺ) wept. The one who was consoling him, either Abu Bakr or ‘Umar, said to him: ‘You are indeed the best of those who glorify Allah with what is due to him.’ The Messenger of Allah (ﷺ) said: ‘The eye weeps and the heart grieves, but we do not say anything that angers the Lord. Were it not that death is something that inevitably comes to all, and that the latter will surely join the former, then we
Grade:

Hadith #1324 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Your brother has been killed.” She said: “May Allah have mercy on him. Inna lillahi wa inna ilayhi raji’un (Truly, to Allah we belong and truly, to Him we shall return).” They said: “Your husband has been killed.” She said: “O grief!” The Messenger of Allah (ﷺ) said: “The woman has a strong love for her husband, which she does not have for anything else.”
Grade:

Hadith #1325 - Sunan Ibn Majah - Abbad bin Tameem Mazni; Abdullah bin Abi Bakr bin Muh. b. 'Amr عبد الله بن أبي بكر بن محمد بن عمرو; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Tameem bin Zayd/Ghaziya Mazni (Sunan Ibn Majah)
“But there is no one to weep for Hamzah.” So the women of Ansar started to weep for Hamzah. The Messenger of Allah (ﷺ) woke up and said, ‘Woe to them, have they not gone home yet? Tell them to go home and not to weep for anyone who dies after this day.’”
Grade:

Hadith #1326 - Sunan Ibn Majah - Abbad bin Tameem Mazni; Abu Bakr bin Muhammad bin 'Amr bin Hazm أبو بكر بن محمد بن عمرو بن حزم; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade eulogies.”
Grade:

Hadith #1327 - Sunan Ibn Majah - Abu Hurairah; Ahmed bin al-Azhar bin Mny' أحمد بن الأزهر بن منيع; al-Nu'man bin Bashir ibn Sa'd; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد (Sunan Ibn Majah)
“The deceased is punished for the wailing over him.”
Grade:

Hadith #1328 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Salm bin Abi al-Ja'd سالم بن أبي الجعد; Sharhbayl bin al-Samat; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
“The deceased is punished for the weeping of the living. If they say: ‘O my strength, O he who clothed us, O my help, O my rock,’ and so on, he is rebuked and it is said: ‘Were you really like that? Were you really like that?’” Asid said: “I said: ‘Subhan-Allah! Allah says: “And no bearer of burdens shall another’s burden (35:18).” He said: “Woe to you, I tell you that Abu Musa narrated to me from the Messenger of Allah (ﷺ), and you think that Abu Musa was telling lies
Grade:

Hadith #1329 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; al-Hasan bin al-Rabi' al-Bajli الحسن بن الربيع; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; ibn Abbas (Sunan Ibn Majah)
“A Jewish woman had died, and the Prophet (ﷺ) heard the weeping for her. He said: ‘Her family is weeping for her, and she is being punished in her grave.’”
Grade:

Hadith #1330 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Bashayr bin Nahayk بشير بن نهيك السدوسي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Ibn Majah)
“Patience should come with the first shock.”
Grade:

Hadith #1331 - Sunan Ibn Majah - Ahmed bin al-Azhar bin Mny' أحمد بن الأزهر بن منيع; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Umar bin Hamza bin 'Abdullah عمر بن حمزة بن عبد الله بن عمر (Sunan Ibn Majah)
“Allah says: ‘O son of Adam! If you are patient and seek reward at the moment of first shock, I will not approve of any reward for you less than Paradise.’”
Grade:

Hadith #1332 - Sunan Ibn Majah - Ata' bin Abi Rabah عطاء بن أبي رباح; Ayoub al-Sakhtiyani أيوب السختياني; ibn Abbas; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“There is no Muslim who is stricken with a calamity and reacts by saying as Allah has commanded: ‘Inna lillahi, wa inna ilayhi raji’un. Allahumma indaka ahtasabtu musibati, fajurni fiha, wa ‘awwidni minha (Truly, to Allah we belong and truly, to Him we shall return. O Allah, with You I seek reward for my calamity, so reward me for it and compensate me),’ but Allah will reward him for that and compensate him with something better than it.” She said: “When Abu Salamah died, I remembe
Grade:

Hadith #1333 - Sunan Ibn Majah - Abdur Rahman bin 'Abdul Malik bin Shayb عبد الرحمن بن عبد الملك بن شيبة; al-Hasan bin Muslim bin Yanaq الحسن بن مسلم بن يناق; ibn Abbas; Ibn Jurayj ابن جريج; Tawus bin Kaysan طاوس; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) opened a door that was between him and the people or drew back a curtain and he saw the people praying behind Abu Bakr. He praised Allah for what he saw of their good situation and hoped that Allah succeed him by what he saw in them.* He said: ‘O people, whoever among the people or among the believers is stricken with a calamity, then let him console himself with the loss of me, for no one among my nation will be stricken with any calamity worse than my loss.’
Grade:

Hadith #1334 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Isma'il bin Raja'a bin Rabi'a al-Zubaidi إسماعيل بن رجاء بن ربيعة الزبيدي; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Qays bin Muslim al-Jadli قيس بن مسلم الجدلي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Tariq bin Shahab (Sunan Ibn Majah)
The Prophet (ﷺ) said: “Whoever was stricken with a calamity and when he remembers it he says ‘Inna lillahi, wa inna ilayhi raji’un (Truly, to Allah we belong and truly, to Him we shall return),’ even though it happened a long time ago, Allah will record for him a reward like that of the day it befell him.”
Grade:

Hadith #1335 - Sunan Ibn Majah - Hammad bin Usamah حماد بن أسامة - أبو أسامة; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“I heard ‘Abdullah bin Abu Bakr bin Muhammad bin ‘Amr bin Hazm narrating from his father, from his grandfather, that the Prophet (ﷺ) said: ‘There is no believer who consoles for his brother for a calamity, but Allah will clothe him with garments of honor on the Day of Resurrection.’”
Grade:

Hadith #1336 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Whoever consoles a person stricken by calamity will have a reward equal to his.’”
Grade:

Hadith #1337 - Sunan Ibn Majah - Abdullah bin Mubarak عبد الله بن المبارك; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Ibn Majah)
“No man who loses three of his children will ever enter the Fire, except in fulfillment of the oath (of Allah).”*
Grade:

Hadith #1338 - Sunan Ibn Majah - Kathir bin 'Abdullah كثير بن عبد الله بن عمرو بن عوف; Muhammad bin Khalid bin Athmh محمد بن خالد بن عثمة (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘There is no Muslim, three of whose children die before reaching the age of puberty, but they will meet him at the eight gates of Paradise and whichever one he wants he will enter through it.’”
Grade:

Hadith #1339 - Sunan Ibn Majah - Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Hrmlh bin Yahya bin حرملة بن يحيى; Khalid bin Yazid خالد بن يزيد الجمحي الإسكندراني; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“There are no two Muslims (mother and father), three of whose children die before reaching the age of puberty, but Allah will admit them to Paradise by virtue of His mercy towards them.”
Grade:

Hadith #1340 - Sunan Ibn Majah - al-Nu'man bin Bashir ibn Sa'd; Habib bin Salm al-Ansari حبيب بن سالم الأنصاري مولى; Ibrahim bin Muhammad إبراهيم بن محمد بن المنتشر; Muhammad bin al-Muntashir bin al-Ajda' محمد بن المنتشر بن الأجدع; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“Whoever sends fourth three of his children who had not reached the age of puberty, they will be a strong fortification for him against the Fire.” Abu Dharr said: “I sent forth two.” He said: “And two” Ubayy bin Ka’b, the chief of the reciters, said: “I sent forth one.” He said: “Even one.”
Grade:

Hadith #1341 - Sunan Ibn Majah - Dmrh bin Sa'id bin Aby ضمرة بن سعيد بن أبي حنة; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Ibn Majah)
‘A miscarried fetus sent before me is dearer to me than a horseman whom I leave behind.”
Grade:

Hadith #1342 - Sunan Ibn Majah - Abdur Rahman bin 'Abdul Malik bin Shayb عبد الرحمن بن عبد الملك بن شيبة; ibn Abbas; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin 'Ubaida bin Nashayt موسى بن عبيدة بن نشيط; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘The miscarried fetus will plead with his Lord if his parents are admitted to Hell. It will be said: “O fetus who pleads with your Lord! Admit your parents to Paradise.” So he will drag them out with his umbilical cord until he admits them to Paradise.’”
Grade:

Hadith #1343 - Sunan Ibn Majah - Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“By the One in Whose Hand is my soul! The miscarried fetus will drag his mother by his umbilical cord to Paradise, if she (was patient and) sought reward (for her loss).”
Grade:

Hadith #1344 - Sunan Ibn Majah - Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan Ibn Majah)
“When news of the death of Ja’far was brought, the Messenger of Allah (ﷺ) said: ‘Prepare food for the family of Ja’far, for there has come to them that which is keeping them busy or something which is keeping them busy.”
Grade:

Hadith #1345 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Nbyt bin Shryt al-'Ashj'y al-Kwfy; Salma bin Nabayt سلمة بن نبيط; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“When Ja’far was killed, the Messenger of Allah (ﷺ) went to his family and said: ‘The family of Ja’far are busy with the matter of their deceased, so prepare food for them.’” (One of the narrators) Abdullah said: “That continued to be the Sunnah, until innovations were introduced, then it was abandoned.”
Grade:

Hadith #1346 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير (Sunan Ibn Majah)
“We used to think that gathering with the family of the deceased and preparing food was a form of wailing.”
Grade:

Hadith #1347 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Ayyad bin 'Abdullah bin Sa'd عياض بن عبد الله بن سعد بن أبي سرح; Da'ud bin Qays al-Fra'a داود بن قيس الفراء الدباغ; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan Ibn Majah)
Dying in a strange land is martyrdom.”
Grade:

Hadith #1348 - Sunan Ibn Majah - Isma'il bin Muslima إسماعيل بن مسلمة بن قعنب الحارثي القعنب; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Yahya bin Hakeem al-Maquuam يحيى بن حكيم المقوم (Sunan Ibn Majah)
“A man died in Al- Madinah, and he was one of those who were born in Al-Madinah. The Prophet (ﷺ) offered the funeral prayer for him and said: “Would that he had died somewhere other than his birthplace.” A man among the people said: “Why, O Messenger of Allah?” He said: “If a man dies somewhere other than his birthplace, a space will be measured for him in Paradise (as big as the distance) from the place where he was born to the place where he died.”
Grade:

Hadith #1349 - Sunan Ibn Majah - Abdullah bin al-Sa'ib; al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; Amr bin Rafa'i al-Advi. Client Of 'Umar عمرو بن رافع العدوي; Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج (Sunan Ibn Majah)
“Whoever dies from a sickness dies as a martyr. He is protected from the torment of the grave and he is granted provision from Paradise morning and evening.”
Grade:

Hadith #1350 - Sunan Ibn Majah - Ady bin Thabit al-Ansari عدي بن ثابت الأنصاري الكوفي; ibn Abbas; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sa'id bin Jubayr سعيد بن جبير الأسدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Ibn Majah)
“Breaking the bones of the deceased is like breaking his bones when he is alive.”
Grade:

Hadith #1351 - Sunan Ibn Majah - Abdullah bin 'Abdur Rahman bin Ya'la عبد الله بن عبد الرحمن بن يعلى; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Breaking the bones of the deceased is, in sin, like breaking his bones when he is alive.”
Grade:

Hadith #1352 - Sunan Ibn Majah - Abdullah bin Muhammad bin 'Aqil عبد الله بن محمد بن عقيل بن أبي طالب; Abu Sa'id al-Khudri; al-Hythm bin Jmyl الهيثم بن جميل; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Ubaidullah bin 'Amr bin Abi Walid عبيد الله بن عمرو بن أبي الوليد (Sunan Ibn Majah)
“I asked ‘Aishah: ‘O mother! Tell me about the sickness of the Messenger of Allah (ﷺ).’ She said: ‘He felt pain and started to spit (over his body), and we began to compare his spittle to the spittle of a person eating raisins. Like a person eating raisins and spitting out the seeds. He used to go around among his wives, but when he became ill, he asked them permission to stay in the house of ‘Aishah and that they should come to him in turns.’ She said: ‘The Messenger of Allah
Grade:

Hadith #1353 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير (Sunan Ibn Majah)
“The Prophet (ﷺ) used to seek refuge using the following words: ‘Adhhibil-ba’s, Rabbin-nas, washfi Antash-shafi, la shifa’a illa shifa’uka, shifa’an la yughadiru saqaman (Take away the affliction, O Lord of mankind, and grant healing, for You are the Healer and there is no healing that leaves no sickness).’ When the Prophet (ﷺ) fell sick with the sickness that would be his last, I took his hand and wiped it over his body and recited these words. He withdrew his hand from mine a
Grade:

Hadith #1354 - Sunan Ibn Majah - Abdullah bin 'Umar bin Hafs bin 'Asim عبد الله بن عمر بن حفص بن عاصم; Abdur Rahman bin 'Abdullah bin 'Umar عبد الرحمن بن عبد الله بن عمر بن حفص; ibn Umar; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘There is no Prophet who fell sick but he was given the choice between this world and the Hereafter.’ She said: ‘When he became sick with the illness that would be his last, (his voice) became hoarse and I heard him say, “In the company of those on whom Allah has bestowed His grace, of the Prophets, the true believers, the martyrs, and the righteous.’” Then I knew that he had been given the choice.”
Grade:

Hadith #1355 - Sunan Ibn Majah - Abu Da'ud أبو داود السجستاني الأزدي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Yahya bin Hakeem al-Maquuam يحيى بن حكيم المقوم; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Ibn Majah)
“The wives of the Prophet (ﷺ) gathered together and not one of them lagged behind. Fatimah came, and her gait was like that of the Messenger of Allah (ﷺ). He said, ‘Welcome to my daughter.’ Then he made her sit to his left, and he whispered something to her, and she smiled. I said to her: ‘What made you weep?’ She said: ‘I will not disclose the secret of the Messenger of Allah (ﷺ).’ I said: ‘I never saw joy so close to grief as I saw today.’ When she wept I said: ‘Did t
Grade:

Hadith #1356 - Sunan Ibn Majah - Abdul 'Aziz bin al-Khtab عبد العزيز بن الخطاب الكوفي أبو الحسن; Muhammad bin 'Ubaidullah bin Abi Rafi' محمد بن عبيد الله بن أبي رافع; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Ibn Majah)
“I never saw anyone suffer more pain than the Messenger of Allah (ﷺ).”
Grade:

Hadith #1357 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير (Sunan Ibn Majah)
“I saw the Messenger of Allah (ﷺ) when he was dying, and there was a bowl of water next to him. He put his hand in the vessel and wiped his face with the water, and said: ‘O Allah, help me to bear the agonies of death.’”
Grade:

Hadith #1358 - Sunan Ibn Majah - Abdullah bin 'Umar bin Hafs bin 'Asim عبد الله بن عمر بن حفص بن عاصم; ibn Umar; Nafie' نافع مولى ابن عمر; Salm bin Qutayba, Abu Qutayba سلم بن قتيبة الشعيري - أبو قتيبة; Yahya bin Hakeem al-Maquuam يحيى بن حكيم المقوم (Sunan Ibn Majah)
“The last glance that I had of the Messenger of Allah (ﷺ) was when he drew back the curtain on Monday, and I saw his face as if it was a page of the Mushaf (Qur’an), and the people were praying behind Abu Bakr. He (Abu Bakr) wanted to move, but he (the Prophet (ﷺ)) gestured to him to stand firm. Then he let the curtain fall, and he died at the end of that day.”
Grade:

Hadith #1359 - Sunan Ibn Majah - Abdul 'Aziz bin al-Khtab عبد العزيز بن الخطاب الكوفي أبو الحسن; Ahmed bin al-Azhar bin Mny' أحمد بن الأزهر بن منيع; Muhammad bin 'Ubaidullah bin Abi Rafi' محمد بن عبيد الله بن أبي رافع; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Ibn Majah)
“The prayer, and those whom your hands possess.”* And he kept on saying it until his tongue could no longer utter any words.
Grade:

Hadith #1360 - Sunan Ibn Majah - Abu Hurairah; Falayh bin Suliaman فليح بن سليمان; Muhammad bin Hmyd bin Hyan محمد بن حميد بن حيان; Sa'id bin al-Harith bin Abi Sa'id سعيد بن الحارث بن أبي سعيد; Yahya bin Wadh يحيى بن واضح (Sunan Ibn Majah)
“They said in ‘Aishah’s presence that ‘Ali was appointed (by the Prophet (ﷺ) before he died), and she said: ‘When was he appointed? He (the Prophet (ﷺ)) was resting against my bosom, or in my lap, and he called for a basin, then he became limp in my lap and died, and I did not realize it. So when did he (ﷺ) appoint him?’”
Grade:

Hadith #1361 - Sunan Ibn Majah - al-Mughira bin Maqsam المغيرة بن مقسم; Amir al-Sha'bi عامر الشعبي; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Swyd bin Sa'id سويد بن سعيد (Sunan Ibn Majah)
“When the Messenger of Allah (ﷺ) passed away, Abu Bakr was with his wife, the daughter of Kharijah, in villages surrounding Al-Madinah. They started to say: ‘The Prophet (ﷺ) has not died, rather he has been overcome with what used to overcome him at the time of Revelation.’ Then Abu Bakr came and uncovered his (the Prophet’s (ﷺ)) face, kissed him between the eyes and said: ‘You are too noble before Allah for Him to cause you to die twice. By Allah, the Messenger of Allah (ﷺ) ha
Grade:

Hadith #1362 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amir al-Sha'bi عامر الشعبي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Qays ibn Sa'd ibn 'Ubadah (Sunan Ibn Majah)
“When they wanted to dig a grave for the Messenger of Allah (ﷺ), they sent for Abu ‘Ubaidah bin Jarrah, who used to dig graves in the manner of the people of Makkah, and they sent for Abu Talhah, who used to dig graves for the people of Al-Madinah, and he used to make a niche in the grave. They sent two messengers to both of them, and they said: ‘O Allah, choose what is best for Your Messenger.’ They found Abu Talhah and brought him, but they did not find Abu ‘Ubaidah. So he dug a gr
Grade:

Hadith #1363 - Sunan Ibn Majah - Aadm bin Abi Iyas آدم بن أبي إياس; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amir al-Sha'bi عامر الشعبي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Jabir ibn 'Abdullah; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية (Sunan Ibn Majah)
“When the Messenger of Allah (ﷺ) suffered the agonies of death that he suffered, Fatimah said: ‘O my father, what a severe agony!’ The Messenger of Allah (ﷺ) said: ‘Your father will suffer no more agony after this day. There has come to your father that which no one can avoid, the death that everyone will encounter until the Day of Resurrection.’”
Grade:

Hadith #1364 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; ibn Umar; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Nafie' نافع مولى ابن عمر (Sunan Ibn Majah)
“Fatimah said to me: ‘O Anas, how did you manage to scatter dust on the Messenger of Allah (ﷺ)?’” And Thabit narrated to us from Anas that Fatimah said: “When the Messenger of Allah (ﷺ) passed away: ‘O my father! To Jibra’il we announce his death; O my father, how much closer he is now to his Lord; O my father, the Paradise of Firdaws is his abode; O my father, he has answered the call of his Lord.” (One of the narrators) Hammad said: “I saw Thabit, when he narrated this Ha
Grade:

Hadith #1365 - Sunan Ibn Majah - Ali bin Ms'hr علي بن مسهر; ibn Umar; Nafie' نافع مولى ابن عمر; Swyd bin Sa'id سويد بن سعيد; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“On the day when the Messenger of Allah (ﷺ) entered Al-Madinah, everything was lit up, and on the day when he died, everything went dark, and no sooner had we dusted off our hands (after burying him) but we felt that our hearts had changed.”*
Grade:

Hadith #1366 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Anas ibn Malik; Harun bin Sa'id هارون بن سعيد; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Ibn Majah)
“We used to be guarded in our speech even with our wives at the time of the Messenger of Allah (ﷺ), fearing that Qur’an may be revealed amongst us, but when the Messenger of Allah (ﷺ) died, we began to speak freely.”
Grade:

Hadith #1367 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hafsa bint Sirin حفصة بنت سيرين; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي; Umm Atiyyah Ansariyah (Sunan Ibn Majah)
“We were with the Messenger of Allah (ﷺ) and we all had a single focus, but when he passed away we started to look here and there (i.e., have different interests).”
Grade:

Hadith #1368 - Sunan Ibn Majah - Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Umm Atiyyah Ansariyah (Sunan Ibn Majah)
“At the time of the Messenger of Allah (ﷺ), if a person stood to pray, his gaze would not go beyond his feet. When the Messenger of Allah (ﷺ) died, if a person stood to pray, his gaze would not go beyond the place where he put his forehead when prostrating. Then Abu Bakr died and it was ‘Umar (the caliph). So, when any person stood to pray his gaze would not go beyond the Qiblah. Then came the time of ‘Uthman bin ‘Affan, and there was Fitnah (tribulation, turmoil), and the people sta
Grade:

Hadith #1369 - Sunan Ibn Majah - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; Abdur Rahman bin 'Abis al-Nakha'i عبد الرحمن بن عابس النخعي; Hafs bin Ghyath حفص بن غياث; Hajjaj bin Artah حجاج بن أرطاة; ibn Abbas (Sunan Ibn Majah)
“After the Messenger of Allah (ﷺ) had died, Abu Bakr said to ‘Umar: ‘Let us go and visit Umm Ayman as the Messenger of Allah (ﷺ) used to visit her.’ He said: ‘When we reached her she wept.’ They said: ‘Why are you weeping? What is with Allah is better for His Messenger.’ She said: ‘I know that what is with Allah is better for His Messenger, but I am weeping because the Revelation from heaven has ceased.’ She moved them to tears and they started to weep with her.”
Grade:

Hadith #1370 - Sunan Ibn Majah - Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Nasr bin 'Ali bin Nasr bin 'Ali; Uthman bin al-Mughira al-Thqfy عثمان بن المغيرة الثقفي مولاهم أبو المغي (Sunan Ibn Majah)
‘The best of your days is Friday. On it Adam was created; on it shall be the Nafakhah,* on it all creation will swoon. So send a great deal of blessing upon me on this day, for your blessing will be presented to me.’ A man said: “O Messenger of Allah! How will our blessing be presented to you when you have disintegrated?” He said: “Allah has forbidden the earth to consume the bodies of the Prophets.”
Grade:

Hadith #1371 - Sunan Ibn Majah - Abdul 'Aziz bin Rafi' عبد العزيز بن رفيع; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; ibn Abbas; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“Send a great deal of blessing upon me on Fridays, for it is witnessed by the angels. No one sends blessing upon me but his blessing will be presented to me, until he finishes them.” A man said: “Even after death?” He said: “Even after death, for Allah has forbidden the earth to consume the bodies of the Prophets, so the Prophet of Allah is alive and receives provision.’”
Grade: